The Influence of Social Capital on Startup Ability of Rural Labor in Nghe An Province, Vietnam - Van Thi Thuy Hoang (Journal of Development Research, 2019)
The research is to identify social capital’s factors that have influence on rural labor’s startup ability in Nghe An. Researching data is collected from 695 rural labors in Nghe An, Vietnam (chosen from 4 districts represented for geographic regions in researching province). Collected data is audited by Binary Logistic model. Analyzed results show that factors belong to social capital have influence on rural labor’s startup ability, such as: home town neighborhood and friends’ influence, relationships, collectives, commercial banks, local policies and regulations, information sharing. The research makes clearly the roles of social capital on rural labor’s startup ability.